Der (Privat-)Wohnungseinbruchdiebstahl nach § 244 Abs. 1 Nr. 3, Abs. 4 StGB Eine Untersuchung unter besonderer Berücksichtigung der Strafzumessung - Obert, Annika (Beiträge zum Strafrecht - Contributions to Criminal Law, 2023)
This study addresses the phenomenon of domestic burglary (§ 244 (1) No. 3, (4) German Criminal Code). Particular emphasis is placed on the realities of criminal sentencing for this offense. Based on a multi-perspective analysis of the various appearances of the phenomenon and its legal classification, the study examines the reform of § 244 GCC and the realities of sentencing in criminal courts for the offense. In particular, discrepancies in sentencing that cannot be adequately explained by differences in factual circumstances of the underlying cases, and deficits in the written reasons for sentencing decisions are highlighted. The study reveals a need for action in the field of criminal sentencing.